Aerobic and strength training in women with overweight, obesity and metabolic disorders in a public health center (Revista horizonte, 2011)
This article determines the effect of 20 weeks of aerobic and/or strength training on anthropometric, cardiovascular, biochemical and physical performance variables. METHODS: Thirty women (35.4Â±7.4 years), sedentary, overweight/obese and metabolic disturbances, were randomly assigned to an aerobic exercise group (GA, n=12), aerobic exercise and strength group (GB, n=11) or a control group (GC, n=9). Anthropometric, biochemical, cardiovascular and physical performance (maximal strength) variables were measured before and after the 20 weeks of the study. The SPSS statistical program (version 15.0 for Windows) was used for data analysis.Â